A Case of Elizabethkingia meningoseptica in the Neonatal Intensive Care Unit - Hadiye Demirbakan; İpek Koçer; Yusuf Ünal Sarıkabadayı (Galenos Yayinevi, 2022)
Elizabethkingia meningoseptica (E. meningoseptica) is a Gramnegative rod that is commonly found in the natural environmental such as soil, plants, foodstuffs, water but is rarely causes human infection. It can cause many clinical conditions like urinary tract infection, meningitis, septicemia, osteomyelitis, necrotizing fasciitis, cellulitis, endocarditis, abdominal abscess, endophthalmitis. Especially immunosuppressed patients and premature infants are risky groups for E. meningoseptica infections. The case was born in another center by cesarean section at 36th gestational week and 2.830 grams and was referred to our hospital with the diagnosis of prematurity, respiratory distress, septicemia, stage 4 intraventricular hemorrhage, hydrocephalus on the 27th postnatal day. The patient had no laboratory findings suggestive of infection other than elevated C-reactive protein level in his routine examinations and an external drainage catheter was implanted because of hydrocephalus. E. meningoseptica was produced in the cerebrospinal fluid sample taken simultaneously. Empirically, meropenem, colistin and vancomycin treatments were initiated and the treatment was not changed according to the culture antibiogram results. Infant was discharged 45 days after hospitalization. Neonatal meningitis caused by E. meningoseptica is fatal in more than half of the cases. In this case, it was aimed to draw attention to the importance of early diagnosis and treatment of microorganism, as well as virulence in terms of clinical course.